Allosteric genetically encoded biosensor for spatiotemporal monitoring of endogenous RNA dynamics in living cells - Deyu Yuan; Huan He; William Song; Duhan Ma; Mingfeng Xie; Yuchun Wang; Jinliang Wei; Qianyu He; Yongli Bao; Yongyun Zhao (Proceedings of the National Academy of Sciences, 2025)
Functions of RNAs are associated with their abundance and unique subcellular localizations. RNA imaging methods for spatiotemporal monitoring of RNA dynamics would facilitate the discovery of unknown functions of RNA, yet improving RNA imaging is challenging because of limitations in methods for directly monitoring native RNA, especially the dynamics of RNA transport and concentration fluctuation. Herein, a label-free and conformation switching–based genetically encoded sensor, termed the Dual-locked RNAtracker (Ducker), that realizes spatiotemporal monitoring of endogenous RNA dynamics in living cells is developed. In this Ducker system, a distinctive strategy is developed by employing one RNA target to initiate an allosteric event that triggers the two locked fluorogenic RNA aptamer (M18 Pepper) to restore the active structure and transmit adequate fluorescence signals. The intracellular circular Ducker (circDucker) realizes high-contrast and unbiased imaging of native mRNA abundance and monitors the fluctuations in RNA concentration. Importantly, it also enables spatiotemporal dynamic tracking of RNA translocation by directly visualizing the process of the mitochondrial lncCyt b undergoing bidirectional nucleocytoplasmic transport, indicating the bidirectional regulatory events in mitochondria and nucleus. Therefore, this highly accessible sensor affords a universal and robust platform for spatiotemporal monitoring of RNA abundance and translocation in complicated dynamic reaction networks in live systems, including mRNA, lncRNA, and microRNA, expanding the current toolbox of RNA research and shedding light on the unknown functions of RNA.